Substantiation and development of an optimal method of minimally invasive posterior interbody stabilization of vertebrae using distraction cages in patients with lumbar spondylolisthesis - Stognii, Artem V.; Piatykop, Volodymyr O.; Babalian, Iurii O. (Ukrainian neurosurgical journal, 2025)
Objective to improve the effectiveness of treatment of patients with lumbar spondylolisthesis, the authors substantiated and developed a novel method of minimally invasive posterior interbody vertebral stabilization (MIPIVS) using distraction cages. Materials and methods: A clinical prospective comparative (controlled) single-center interventional cross-section study was conducted with a subsequent observation phase, as well as preliminary modeling and development of a noveltervention method. The biomechanical model was used to determine the possibility of restoring the functional state of the spine using distraction cages, and the stress-strain state of the structures was analyzed. The clinical part of the study involved 21 patients aged 35 to 68 (Me=56 [LQ=50; UQ=65]) years (15 women and 6 men), divided into three groups: the study group (n=4) treated with the author's method of MIPIVS (patent application No. a202302383 dated May 18, 2023), a comparison group (n=10) with the standard method of MIPIVS, a control group (n=7) treated with other methods of interbody spondylodesis. Patients were examined according to standard protocols. Logistic and statistical analyses were performed using standard nonparametric methods at a critical level of p<0.05. The principles of bioethics and biomedicine were observed. Results: Before and after surgical treatment of patients with degenerative spondylolisthesis of the lumbar spine, the size of the spinal canal was studied and the dynamics of neurological disorders was assessed. The authors developed a novel method of minimally invasive posterior interbody stabilization of vertebrae using distraction cages and determined the possibility of restoring the value of segmental lordosis, parameters of spinal-pelvic balance and sagittal contour of the spine as indicators of the functional state of the spine using a biomechanical model. The analysis also included assessment of the stress-strain state within the "transpedicular structure – spinal motion segment – distraction cage" system. Сonclusions: The proprietary method of MIPIVS using distraction cages, which has been substantiated and developed, will help to improve the effectiveness of treatment for patients with lumbar spondylolisthesis. Further research prospects include clinical testing of the author's MIPIVS method. Цель: повысить эффективность лечения пациентов с поясничным спондилолистезом с помощью малоинвазивной задней межтеловой стабилизации позвонков (МИЗМТСП) с использованием дистракционных кейджей. Материалы и методы. Проведено клиническое проспективное сравнительное (контролируемое) одноцентровое срезовое интервенционное исследование. С помощью биомеханической модели с использованием дистракционных кейджей определены возможности восстановления величины сегментарного лордоза, параметров позвоночно-тазового баланса и сагиттального контура позвоночника как показателей функционального состояния позвоночника, а также проанализировано напряженно-деформированное состояние в системе «транспедикулярная конструкция‒ позвоночный двигательный сегмент ‒ дистракционный кейдж». В клинических исследованиях принял участие 21 пациент (15 женщин и 6 мужчин) в возрасте от 35 до 68 лет (медиана ‒ 56 [50;65] лет), которых распределили на три группы: основную (n=4), в которой использован авторский способ МИЗМТСП (пат. заявка №a202302383 от 18.05.2023 г.), сравнения (n=10), в которой применен стандартный способ МИЗМТСП, контрольную (n=7), в которой использованы другие способы межтелового спондилодеза. Обследование пациентов проведено по стандартным протоколам. Логико-статистический анализ выполнен стандартными непараметрическими методами при критическом уровне р<0,05. В ходе исследования соблюдены принципы биоэтики и биомедицины. Результаты. Изучены размеры позвоночного канала и оценена динамика неврологических нарушений до и после хирургического лечения пациентов с дегенеративным спондилолистезом поясничного отдела позвоночника. Разработан метод МИЗМТСП с использованием дистракционных кейджей. С помощью биомеханической модели определены возможности восстановления величины сегментарного лордоза, параметров позвоночно-тазового баланса и сагиттального контура позвоночника как показателей функционального состояния позвоночника. Проанализировано напряженно-деформированное состояние в системе «транспедикулярная конструкция – позвоночный двигательный сегмент – дистракционный кейдж». Выводы. Использование предлагаемого способа МИЗМТСП с применением дистракционных кейджей будет способствовать повышению эффективности лечения пациентов с поясничным спондилолистезом. Мета: підвищити ефективність лікування пацієнтів із поперековим спондилолістезом за допомогою малоінвазивної задньої міжтілової стабілізації хребців (МІЗМТСХ) із використанням дистракційних кейджів. Матеріали і методи. Проведено клінічне проспективне порівняльне (контрольоване) одноцентрове зрізове інтервенційне дослідження. За допомогою біомеханічної моделі із використанням дистракційних кейджів визначено можливості відновлення величини сегментарного лордозу, параметрів хребтово-тазового балансу та сагітального контуру хребта як показників функціонального стану хребта, а також проаналізовано напружено-деформований стан у системі «транспедикулярна конструкція ‒ хребетний руховий сегмент ‒ дистракційний кейдж». У клінічні дослідження було залучено 21 пацієнта (15 жінок і 6 чоловіків) віком від 32 до 68 років (медіана ‒ 56 [50;65] років), яких розподілили на три групи: основну (n=4), в якій використано авторський спосіб МІЗМТСХ (пат. заявка №a202302383 від 18.05.2023 р.), порівняння (n=10), в якій застосовано стандартний спосіб МІЗМТСХ, контрольну (n=7), в якій використано інші способи міжтілового спондилодезу. Обстеження пацієнтів проведено за стандартними протоколами. Логіко-статистичний аналіз виконано стандартними непараметричними методами за критичного рівня р<0,05. Під час дослідження дотримано принципів біоетики та біомедицини. Результати. Вивчено розміри хребтового каналу та оцінено динаміку неврологічних порушень до та після хірургічного лікування пацієнтів із дегенеративним спондилолістезом поперекового відділу хребта. Розроблено метод МІЗМТСХ із використанням дистракційних кейджів. За допомогою біомеханічної моделі визначено можливості відновлення величини сегментарного лордозу, параметрів хребтово-тазового балансу та сагітального контуру хребта як показників функціонального стану хребта. Проаналізовано напружено-деформований стан у системі «транспедикулярна конструкція ‒ хребетний руховий сегмент ‒ дистракційний кейдж». Висновки. Використання запропонованого способу МІЗМТСХ із застосуванням дистракційних кейджів сприятиме підвищенню ефективності лікування пацієнтів із поперековим спондилолістезом.